Strategi Menggerakkan Festival Warga Studi Kasus Penyelenggaraan Layang Lakbok Art and Culture Festival - Asep Zery Kusmaya; Aton Rustandi Mulyana; St. Sunardi (Universitas Gadjah Mada, 2021)
ABSTRACTA festival is a cultural event that all cultural communities in the world have. One of the festival's functions is to improve the life energy of the cultural community that organizes it. Layang Lakbok Art and Culture Festival is a festival organized by Lakbok residents, Ciamis Regency, West Java. This festival stems from the spirit of a group of young people who are members of the Pematang Sawah Association to develop the post-harvest celebration of Lakbok residents into a bigger event. This idea and spirit then invite all citizens to be involved in the festival production process. The process of spreading ideas, spirit, and the festival production is carried out using the social capital owned by the youth, in particular, and in general by all citizens. The social capital used covers all aspects that are owned by citizens, starting from kinship relations, friendship, habits, actions, conflict management, arts, culinary, and many others. Thus, Layang Lakbok Art and Culture can be said to be a citizen festival that is owned and produced independently by them. The citizen participation aspect is the key to organizing this festival. This research is an attempt to interpret the practices that the author has alone experienced, together with the residents, to be precise in the production process of the Layang Lakbok Art and Culture Festival. For this reason, the research method used was the action research method where the author is directly involved in the process of procuring the Layang Lakbok Festival. This paper is expected to reveal the various participation done by the residents in organizing Layang Lakbok so that how the Layang Lakbok Festival is developed can be better known. ABSTRAKFestival merupakan sebuah peristiwa budaya, yang dimiliki oleh seluruh komunitas budaya di dunia. Salah satu dari fungsi festival adalah memperbaiki energi kehidupan dari komunitas budaya yang menyelenggarakannya. Layang Lakbok Art and Culture Festival adalah Sebuah festival yang diselenggarakan oleh warga Lakbok, Kabupaten Ciamis, Jawa Barat. Festival ini berangkat dari semangat sekelompok anak-anak muda yang tergabung dalam Paguyuban Pematang Sawah dalam mengemas ulang perayaan pasca panen warga Lakbok menjadi eventyang lebih besar. Ide dan semangat ini kemudian dibagikan kepada seluruh warga untuk ikut terlibat dalam proses produksi festival. Proses penyebaran ide, semangat hingga proses produksi festival dilakukan dengan menggunakan modal sosial yang dimiliki oleh anak-anak muda tersebut pada khususnya dan pada umumnya oleh seluruh warga. Modal sosial yang digunakan mencakup seluruh aspek yang dimiliki oleh warga yaitu mulai dari relasi kekerabatan, pertemanan, kebiasaan, tindakan, manajemen konflik, kesenian, kuliner dan lain sebagainya. Jadi Layang Lakbok Art and Culture merupakan sebuah festival warga, yang dimiliki oleh warga dan diproduksi secara mandiri oleh warga. Aspek partisipasi warga menjadi kunci dalam penyelenggaraan festival ini. Penelitian ini adalah upaya memaknai praktik yang telah dialami sendiri oleh penulis bersama warga dalam proses pewujudan Layang Lakbok Art and Culture Festival. Jadi metode penelitian yang digunakan adalah metode penelitian bertindak, di mana penulis terlibat langsung dalam proses pewujudan Layang Lakbok Festival. Lalu tulisan ini diharapkan dapat meraba lapis-lapis partisipasi warga dalam penyelenggaraan Layang Lakbok sehingga dapat dilihat bagaimana sesungguhnya Layang Lakbok Festival digerakkan.